Política de assistência estudantil e educação tecnológica do campo: estratégias de permanência escolar - LIMA, Maria Eliane de (Instituto Federal de Educação Ciência e Tecnologia do Pará, 2023)
This dissertation presents a discussion to perform an intervention appropriate to the problem of retention of the students of Agricultural Technician Course Integrated into the high school of the Rural Campus of Marabá (CRMB) – Instituto federal do Pará (IFPA). Was taken as an element of analysis and interpretation the perception of social actors investigated (students, administrative technicians and managers of the Campus).To meet this reality in order to create strategies for school residency under the Student Assistance Policy (PAE) in the context of the field's technological education. The main objective was to understand what are the most relevant factors that lead to a high number of students failed (which did not achieve the minimum average) and retained (that were disapproved in three or more and retained (which were disapproved in three or more subjects, in addition to the significant number of school dropouts in the last classes of the CRMB, considering the context of the rural technological education. Thus, the origin of these students was verified and where they are inserted, emphasizing that the majority is of farmers and children of farmers from the rural area, residents in settlements of the Land Reform and campsites located in the municipality of Marabá-Pará and other municipalities in the Paraense southeast . Data from the field were analyzed through consultations with the documents and institutional reports, which were complemented with essential information seized with students and teachers, which made it possible to access the a significant number of different social actors who work directly in teaching-learning, and from their testimonies the intervention project was elaborated, "product" of this masters that will be presented to the institution in order to implement it in the CRMB, as a purpose to solve the problems of retention